2022
DOI: 10.1177/10781552221125871
|View full text |Cite
|
Sign up to set email alerts
|

Melphalan on day -1 versus day -2 in patients with plasma cell disorders undergoing autologous stem cell transplant

Abstract: High-dose melphalan-based autologous stem cell transplant (ASCT) remains a standard of care for plasma cell disorders (PCDs). Currently, there is variability in the literature surrounding the timing of melphalan administration to avoid potential cytotoxic effects, although the administration has been safely proposed when given at least 8 hours prior to stem cell infusion. The objectives of this study were to assess differences in safety and efficacy outcomes between day -1 and day -2 single-dose melphalan admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…D-2 dosing was historically used to avoid potential effects of residual melphalan on the stem cell graft. Two retrospective studies of MM patients undergoing ASCT observed no difference in time to platelet and neutrophil engraftment between D-1 and D-2 melphalan dosing ( 7 9 ), whereas a study of 367 patients showed delays in both platelet and neutrophil engraftment with D-1 melphalan ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…D-2 dosing was historically used to avoid potential effects of residual melphalan on the stem cell graft. Two retrospective studies of MM patients undergoing ASCT observed no difference in time to platelet and neutrophil engraftment between D-1 and D-2 melphalan dosing ( 7 9 ), whereas a study of 367 patients showed delays in both platelet and neutrophil engraftment with D-1 melphalan ( 10 ).…”
Section: Introductionmentioning
confidence: 99%